ANALISIS MANAGEMENT BANDWIDTH DAN FIREWALL DENGAN ROUTER MIKROTIK PADA PT. BCA MULTIFINANCE - Astrid Noviriandini; Hermanto Hermanto; Diah Ayu Ambarsari; Didy Eriawan (Jurnal Teknik dan Science, 2022)
The internet network is something that is familiar to mankind in this current century, where the need for internet access is currently very high, both to find information, articles and the latest knowledge. In general, many agencies have integrated the internet network into their daily activities in the work environment. PT. BCA MULTIFINANCE (BCAMF), is an institution that is engaged in vehicle and multipurpose loan financing. In order for computer network performance to be optimized, it is necessary to have management on the network that is able to handle congested and slow connection problems. The solutions that will be used include the addition of switches and bandwidth management and firewalls using a mikrotik router. The mechanism is that the proxy router regulates bandwidth sharing and IP blocking for each user. The choice of bandwidth management and firewall methods is because these methods meet the criteria for managing access speed for each client or network.